Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/toh.2020.3038937
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Friction Modulation From the Ultrasonic Mechanical Impedance

Abstract: Ultrasonic surface-haptic touchscreens produce compelling tactile sensations directly on the users' fingertips. The tactile sensations stem from the modulation of friction produced by acoustic radiation pressure, which reduces the contact between the skin and the glass plate. During this process, some of the vibrations are partly absorbed by the tissues, resulting in a conspicuous change in the vibration amplitude of the plate upon contact with the finger, which manifests as a net change in the system mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This shows for the first time that small lateral movements as a part of natural motor control during grasping helps inform our perception of friction between the finger pad skin and the object being touched. Our findings can inform engineers of how programmed movement jitter may improve the sensitivity of tactile sensors (Khamis et al, 2019; Huloux et al, 2021; Khamis et al, 2021a) which could measure friction (Chen et al, 2018; Khamis et al, 2018; Ulloa et al, 2022) and in designing tactile displays which make use of friction modulation principles (Gueorguiev et al, 2017; Vardar et al, 2017). This study also has implications in the design of neural prostheses and extends the understanding of tactile sensorimotor control strategies required for dexterous object manipulation (Suresh et al, 2020; Bensmaia et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…This shows for the first time that small lateral movements as a part of natural motor control during grasping helps inform our perception of friction between the finger pad skin and the object being touched. Our findings can inform engineers of how programmed movement jitter may improve the sensitivity of tactile sensors (Khamis et al, 2019; Huloux et al, 2021; Khamis et al, 2021a) which could measure friction (Chen et al, 2018; Khamis et al, 2018; Ulloa et al, 2022) and in designing tactile displays which make use of friction modulation principles (Gueorguiev et al, 2017; Vardar et al, 2017). This study also has implications in the design of neural prostheses and extends the understanding of tactile sensorimotor control strategies required for dexterous object manipulation (Suresh et al, 2020; Bensmaia et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…The frequency response was measured with an accelerometer (ICP Accelerometer 352A71, PCB Piezotronics, Buffalo, USA) fixed between the actuator and the index finger of the experimenter. It should be noted that the impedance of the finger grip attenuates the resonance of the actuator [47] compared to the free oscillations condition provided in the accelerometer reference guide. The differences in frequency response among individuals holding the actuator are negligible concerning perception [48].…”
Section: B Vibration Renderingmentioning
confidence: 99%
“…It would be desirable to be able to measure the amplitude of the vibration under this situation; however, it is difficult to do this using the current setup. For example, a method for estimating the amplitude of the vibration by placing a sensor on a vibrating glass was shown in an existing experiment on the change in friction by ultrasonic waves [28]. However, it was found that the entire polystyrene foam plate was not excited in a certain resonant mode, but rather in a narrow area of approximately 2 cm in diameter near the focal point of oscillation.…”
Section: B Difficulty In Measurement Of Displacement When Touchedmentioning
confidence: 99%